Coffee Consumption With The Incident Of Gastritis: Literature Review - Santoso, Puguh (Chakra Brahmanda Lentera Institute, 2023)
Background: Gastritis is a stomach health problem that begins with inflammation of the gastric mucosa caused by infection with the Helicobacter pylori germ and is the most common disease. One cause of gastritis is the habit of drinking coffee. The habit of drinking coffee (caffeine) for a long period with a frequent frequency, namely > three glasses/day, can trigger an increase in stomach acid, irritating the mucosa or the stomach wall. This literature review aims to analyze the relationship between coffee consumption and the incidence of gastritis Methods: Literature obtained from SINTA, PUBMED, Garuda, and Google Scholar databases. Nine literature reviews used several designs, namely descriptive exploratory, cross-sectional, descriptive cross-sectional study, case-control, descriptive-analytical, and descriptive from 2013-2023; then PICO analysis was carried out. Results: The caffeine content in coffee can stimulate the production of stomach acid, which can trigger gastritis. Inflammation will occur continuously if the stomach is frequently exposed to irritants such as coffee. The inflamed tissue is then filled with fibrin tissue, which can cause loss of the gastric mucosal layer and atrophy. Conclusion: The study showed that coffee influenced the incidence of gastritis.